Antibacterial Properties of Extracts Derived from the Leaves of Black Locust (Robinia pseudoacacia L.) - Tkachenko, Halina; Lukash, Oleksandr; Kurhaluk, Natalia (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2025)
The growing resistance of bacterial pathogens to conventional antibiotics has intensified the search for alternative antimicrobial agents, particularly those derived from plants. Robinia pseudoacacia L. (black locust) is a plant known for its diverse phytochemical profile, including compounds with potential antibacterial activity. The aim of this study was to evaluate the antimicrobial effects of R. pseudoacacia extract against selected Gram-positive and Gram-negative bacterial strains of clinical relevance. The antibacterial activity was evaluated using the Kirby-Bauer disc diffusion method on six bacterial strains: Gram-positive strains such as Enterococcus faecalis (Andrewes and Horder) Schleifer and Kilpper-Balz (ATCC®51299™) (resistant to vancomycin; sensitive to teicoplanin), Enterococcus faecalis (Andrewes and Horder) Schleifer and Kilpper-Balz (ATCC®29212™), Staphylococcus aureus subsp. aureus Rosenbach ATCC®29213™, Staphylococcus aureus NCTC12493™, and Gram-negative strains such as Pseudomonas aeruginosa (Schroeter) Migula ATCC®27853™, Escherichia coli (Migula) Castellani and Chalmers ATCC®25922™, and Escherichia coli (Migula) Castellani and Chalmers ATCC®35218™ strains. The extract showed significant inhibitory effects on Enterococcus faecalis ATCC®51299™ and ATCC®29212™, with statistically significant increases in inhibition zones of 40.3% and 63.6%, respectively (p < 0.05). In contrast, Staphylococcus aureus strains (ATCC®29213™ and NCTC12493™) and Gram-negative bacteria including Escherichia coli and Pseudomonas aeruginosa showed minimal or non-significant responses to the extract. These results suggest that R. pseudoacacia extract contains bioactive compounds with selective antibacterial activity against E. faecalis, highlighting its potential as a natural source of antimicrobial agents. Further studies are required to identify the active compounds and elucidate their mechanisms of action.